Regulating the Unregulated: Legal Gaps in Green Finance, Light Pollution, and Surrogacy Under Civil Law Frameworks - Nasywa Nidaul Azmi; Mazaya Luthfillah (Cv. Kayaswara, 2026)
The rapid evolution of global socio-economic and environmental realities has outpaced the development of civil law frameworks in several critical domains. This article examines three distinct yet interconnected areas of legal underregulation: green finance, light pollution, and surrogacy. Through a doctrinal legal analysis complemented by a comparative law approach, this study identifies the structural deficiencies in existing civil law systems that leave these domains inadequately governed. In the realm of green finance, the absence of standardized taxonomies and enforceable obligations creates opportunities for greenwashing and undermines sustainable development goals. Regarding light pollution, the lack of recognition as a legally cognizable harm within civil liability frameworks leaves affected communities without meaningful remedies. In the case of surrogacy, inconsistent legal treatment across jurisdictions generates conflicts of law, particularly concerning the legal parentage and citizenship of children born through surrogacy arrangements. This article argues that the traditional principles of civil law, including the doctrines of nuisance, contractual freedom, and parental rights, require substantial reinterpretation and legislative reform to address these contemporary challenges. The study proposes a unified regulatory framework grounded in civil law principles that can accommodate the unique characteristics of each domain while maintaining internal coherence.